Reclaiming Lalon and his philosophy: Deho-Totto, transcendentalism, and our academia - Masud, Syed Farhan (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.